Retrospective national cohort study of pregnancy outcomes for women with type 1 and type 2 diabetes mellitus in Republic of Ireland. (July 2022) - Newman, Christine; Egan, Aoife M.; Ahern, Tomas; Al-Kiyumi, Maisa; Bacon, Siobhan; Bahaeldein, Elgelani; Balan, Gabriela; Brassill, Mary-Jane; Breslin, Emily; Brosnan, Elizabeth; Carmody, Louise; Clarke, Hilda; et al.
Abstract: Aim: Report the outcomes of pregnant women with type 1 and type 2 diabetes and to identify modifiable and non-modifiable factors associated with poor outcomes. Methods: Retrospective analysis of pregnancy preparedness, pregnancy care and outcomes in the Republic of Ireland from 2015 to 2020 and subsequent multivariate analysis. Results: In total 1104 pregnancies were included. Less than one third attended pre-pregnancy care (PPC), mean first trimester haemoglobin A1c was 7.2 ± 3.6% (55.5 ± 15.7 mmol/mol) and 52% received pre-conceptual folic acid. Poor preparation translated into poorer pregnancy outcomes. Livebirth rates (80%) were comparable to the background population however stillbirth rates were 8.7/1000 (four times the national rate). Congenital anomalies occurred in 42.5/1000 births (1.5 times the background rate). More than half of infants were large for gestational age and 47% were admitted to critical care. Multivariate analyses showed strong associations between non-attendance at PPC, poor glycaemic control and critical care admission (adjusted odds ratio of 1.68 (1.48–1.96) and 1.61 (1.43–1.86), p < 0.05 respectively) for women with type 1 diabetes. Smoking and teratogenic medications were also associated with critical care admission and hypertensive disorders of pregnancy. Conclusion: Pregnancy outcomes in women with diabetes are suboptimal. Significant effort is needed to optimize the modifiable factors identified in this study.